Transparency and Political Parties. The ‹‹Other obligated subjects›› - Moretón Toquero, Mª Aránzazu (EUNOMÍA. Revista en Cultura de la Legalidad, 2022)
In the context of measures to combat public corruption, efforts have been made to anticipate the protection barrier by using advertising as a means of discouraging improper behaviour, but also as a means of controlling the proper functioning of institutions. Preceded by an intense debate, political parties were finally included, albeit in a limited way, in the scope of application of Law 19/2013 on Transparency, Access to Public Information and Good Governance.This work focuses not only on the justification and the need to extend the field of transparency to political formations, but also, in the critical analysis of the coherence and sufficiency of the set of publicity obligations to which political formations are subject.
Keywords: corruption; transparency; political parties; accountability; control; participation